Proyecto de factibilidad para la implementación de una empresa productora y comercializadora de pasta de cacao en el cantón Lago Agrio, provincia de Sucumbíos - Quintanilla Mantuano, Diana Mercedes (2017)
This paper aims at implementing a "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A COMPANY PRODUCER AND DISTRIBUTOR OF PASTA COCOA IN Lago Agrio Canton, Sucumbios province," considering the business opportunity with local products such as cocoa increasing value added, improvement of raw material prices in the market and the opportunity to increase workplaces in the area of influence based on the analysis of all factors that will intervene in the creation of the company. In order to determine the feasibility of the implementation of the company, the techniques of data collection were evaluated, such as the survey of the families of the canton Lago Agrio with a sample of 379 and the suppliers of the commercial premises in a number of 22, of the methods, such as the deductive method, the inductive method, the statistical method and the statistical method. In the market study, we proceeded to tabulate and analyze the surveys, determining the potential demand of 27,989 families, the actual demand 17,913 families, effective demand of 644,867 cocoa paste, the supply of 28,368 cocoa paste units of 500gr. and the unsatisfied demand of 616,499 units of 500gr cocoa paste. This information allows to determine that the project can and should be executed, for the results obtained in the analysis of the demand, supply and marketing levels of this product. The installed capacity of the project determines that the company will be able to produce 345,540 cocoa paste units of 500gr., And its used capacity will be 207,324 cocoa paste units of 500gr., Which represents 60% of the capacity used for the first year, in addition determines the location of the same that will be located in the canton Lago Agrio, in the streets Av. Quito Km 3. Next, the engineering of the project is developed, determining the production process, which demands the use of suitable machines and equipment, which will guarantee a quality product at moderate prices, process diagrams, operational and management characteristics, technical requirements such as equipment, facilities, furniture and appliances. Likewise, an administrative study was carried out, being determined as a Limited Liability Company, and with the functional organizational structure at the hierarchical levels: Legislative, Executive, Adviser, Auxiliary or Support and Operational Level, as well as function manuals, organizational charts; which will serve as a guideline to implement a good organization, so that the following personnel will be counted: Manager, an Accountant Secretary, who will be part of the Administrative staff, and the operational personnel distributed as follows: Three Workers, a production manager, and a seller. The project reaches an investment of 130,254.14 dollars and will be financed with a contribution of the partners 50.10% of the total of the investment that corresponds to 65.254,14 dollars and a loan that will maintain the project with Banecuador will constitute the 49,90 % corresponding to $ 65,000.00 at 4 year term at 11% annual interest. The financial evaluation presents the following results: According to the NPV of the present project gives us a positive value of 250.256,17 dollars, which indicates that the project or investment is convenient. For the present project, the IRR is 54.46%, with this value being satisfactory to carry out the project, the time that would be required to recover the original investment would be 2 years, 9 months and 27 days, for the present project, the sensitivity values are less than one, therefore the changes in costs and revenues increased by 17.12% and 13.17%, respectively, ie the project is not sensitive to these changes. In addition, an environmental impact study was applied which includes all environmental aspects related to operational activities and other complementary activities that may directly or indirectly affect the environmental environment, health and safety of personnel and the population in general. Subsequently, the most significant conclusions and recommendations of the project.